Pengaruh Kompetensi, Pengalaman dan Etika Profesi Auditor Terhadap Tingkat Materialitas dalam Pemeriksaan Laporan Keuangan: Studi Kasus pada KAP di Surabaya - Warda Verda Verina; Hero Priono (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to examine and analyze the influence of auditors' competence, experience and professional ethics on the level of materiality in auditing financial reports at Public Accounting Firms in Surabaya. This research uses quantitative research with multiple linear regression techniques. The population in this study was all auditors at the Public Accounting Firm in Surabaya totaling 160 auditors. The sample in this study used simple random sampling, totaling 62 auditors from 12 Public Accounting Firms (KAP) in Surabaya and were willing to fill out the questionnaire. Based on the research results, it shows that the competence and professional ethics of auditors partially have a significant effect on the level of materiality, while experience has no effect on the level of materiality. And the competency, experience and professional ethics of auditors simultaneously have a significant effect on the level of materiality.